(untitled) (Linguostylistic Studies, 2018)
The article highlights an issue of the spiritual relationship of a person and his language, and hence the national-linguistic behavior of the individual and community. The issues are topical in the current linguistic studies. The translator plays an important role in the perception of the linguistic picture of the world created by one people by representatives of another nation, especially when talking about cognition of the foreign reality via the literary text, where the word reflects the national-linguistic behavior of the authors of the original and translated text. The article examines the peculiarities of P. Kulish’s national-linguistic behavior as a pioneer of the Ukrainian translation school, whose creative work has repeatedly been the subject of research by scientists in various fields of knowledge. In accordance with the purpose and objectives of the study, the author argues the definition of the concept of national-linguistic behavior. The typological and nationally-marked features of addresses in the Ukrainian speech discourse and specific features of address constructions translation are compared and generalized according to the theoretical provisions of scholars. The emphasis is laid on the word-forming and lexical capabilities of transferring addresses in Ukrainian translation. The most frequent techniques are transcribing personal and some general foreign appellatives in accordance with the spelling norms, existing in the time of P. Kulish, rendering honoratives/honorifics by Ukrainian equivalents, or sporadically by transliteration, using diminutives and emotive addresses with nationally-marked lexemes of that time, or emotive attributes in the structure of commonly used addressing constructions, typical of the Ukrainians.